High thermoelectric performance of TlInSe3 with ultra-low lattice thermal conductivity - Yin, Xixi; Zhou, Lang; Wang, Qi; Liao, Yangfang; Lv, Bing (Frontiers in Physics, 2023)
The thermoelectric (TE) materials with excellent thermoelectric figure of merit (ZT) are an effective way to alleviate energy pressure and protect the environment. Herein, we systematically study the electronic and phonon transport properties of two-dimensional (2D) novel TlInSe3 by the first-principles method combined with the Boltzmann transport theory (BTE). The calculation results show that 2D TlInSe3 has an excellent power factor (0.81×10-2 W/mK2) and ultra-low lattice thermal conductivity (0.46 W/mK) at room temperature. We find that the lower phonon group velocity and the large phonon anharmonicity are the main factors leading to the ultra-low lattice thermal conductivity of TlInSe3. Meanwhile, by discussing the acoustic-optical scattering and Crystal Orbital Hamilton Population (COHP), we attribute low phonon group velocity to the increase of (the out-of-plan acoustic mode (ZA)+optical mode (O)→O (ZA+O→O), the in-plane transverse acoustic mode (TA)+O→O (TA+O→O), and the in-plane longitudinal acoustic mode (LA)+O→O (LA+O→O)) scattering rates and the filling of anti-bonding states lead to weak Tl-Se chemical bonds, which further suppresses the lattice thermal conductivity. Based on the analysis of electron and phonon transport properties, 2D TlInSe3, as a novel TE material, exhibits a ZT value as high as 4.15 at 500 K. Our research results show that TlInSe3 is a potential TE material, and the relevant analysis is helpful for the exploration of new TE materials